Primary osteosarcoma of the breast during lactation: a case report and literature review - Zhuo, Huifang; Duan, Yubei; Dong, Shuangshuang; Zhang, Jun; Wang, Zijing; Meng, Lian; Wang, Chenyan; Li, Man; Yang, Xiaotian (Frontiers in Oncology, 2024)
Primary osteosarcoma of the breast (POB) is an aggressive and exceedingly rare tumor, and cases with onset during lactation are extremely rare. The exact mechanism of POB development remains unclear. They may originate from totipotent mesenchymal cells in the breast stroma or may be the result of neoplastic transformation of prior breast lesions. Here, we present the case of a 40-year-old Chinese woman who was found with a palpable tumor measuring approximately 3 cm in diameter in her right breast while breastfeeding 4 months post-partum. The lactating woman was misdiagnosed with lactational mastitis during her initial visit to a community hospital. However, due to negative bacterial cultures and ineffective anti-infective treatment, later on the patient was taken to a more advanced hospital where a tissue biopsy was taken. The superior hospital considered that it might be a malignant tumor and performed local excision of the breast mass, leading to a final pathological diagnosis of POB. This is the first reported case of primary osteosarcoma during breastfeeding. We hope that this case report will improve readers’ understanding of the diagnosis and differential diagnosis of POB, especially for patients with atypical clinical symptoms and imaging findings, which should not be taken lightly.